Shared Margins : An Ethnography with Writers in Alexandria after the Revolution. - Schielke, Samuli. (ZMO-Studien Series, 2021)
The refereed series ZMO-Studien publishes monographs and edited volumes which mirror the interdisciplinary research programme and approach of the Leibniz-Zentrum Moderner Orient.